PENGARUH TERAPI SENAM AEROBIC LOW IMPACT TERHADAP SKOR AGRESSION SELF-CONTROL PADA PASIEN DENGAN RISIKO PERILAKU KEKERASAN DI RUANG SAKURA RSUD BANYUMAS - harki isnuur akhmad; - handoyo; tulus setiono (Jurnal Ilmiah Kesehatan Keperawatan, 2011)
Aggression refers to behavior between members of the same species that is intended to cause humiliation, pain, or harm. Based on, some studies show that exercise therapy could reduce aggression level for mentally ill.This study applied Low Impact-Aerobic exercise therapy to reduce Agression Self-Control score of patients with risk for violent behaviour. The aim of this study was to show the impact of Low Impact-Aerobic exercise therapy toward Agression Self-Control score of patients with risk for violent behaviour in Sakura Room RSUD Banyumas. Quasy-Experiment study, pre-test–post-test with control group design was applied. The number of respondents was 60 patients with risk for violent behaviour and chosen by purposive sampling method. Experimental groups were trained by Low Impact-Aerobic exercise therapy and control groups were given usual therapy based on standard operating procedure in the hospital. Samples were divided into 30 experimental and 30 control groups. Paired t-test and t-test 2n independent statistical analysis were used to analyze the data. The result shows that Aggression Self-Control score in control groups during pre and post test were 52, 3 and 52, 7 respectively. Meanwhile, paired t test shows at (t=0, 26, p=0, 79). This result indicates that there was no significant differences of Aggression Self-Control score in the control groups. Furthermore, Aggression Self-Control score in the experimental groups show at 53, 3 and 73, 5 and statistical test shows at (t=5, 32, p=0, 00). That means, there was significant differences of Aggression Self-Control score in the experimental groups. By t-test 2n Independent show at  (t=7,74, p=0,00) when comparing between control and experimental groups. This statistical analysis explained that there was significant differences of  Aggression Self-Control score of control and experimental groups. The study revealed that Low Impact-Aerobic exercise therapy could reduce Agression Self-Control score of patients with risk for violent behaviour in Sakura Room RSUD Banyumas. Keywords: Low Impact- Aerobic, Aggression Self-Control, Risk for Violent